Proposal of an information architecture to integrate rights-holders’ information into a comprehensive electronic clinical file - Fuentes-Penna, Alejandro (2013)
This investigation has the objective of proposing a methodology to integrate the information of right-holders into a single electronic file, considering the different entities where information related to the state of health of each patient can be generated. The incorporation of the methodology ITIL is proposed (administration of technological services) as a structure to link the information generated in the different areas of a health center and integrate them into a single file. With this, different statistical techniques or artificial intelligence may be applied to find the relationship between the different factors that may contribute to an illness.